Carbon cycling in soil. Issue 10 (1st December 2004) - Johnston, Carol A.; Groffman, Peter; Breshears, David D.; Cardon, Zoe G.; Currie, William; Emanuel, William; Gaudinski, Julia; Jackson, Robert B.; Lajtha, Kate; Nadelhoffer, Knute; Nelson, David; Post, W Mac; et al.
Abstract : As yet, nobody knows what effects climate change will have on soil carbon reserves, or how those changes will affect the global carbon cycle. Soils are the primary terrestrial repository for carbon, so minor changes in the balance between belowground carbon storage and release could have major impacts on greenhouse gases. Soil fauna, roots, fungi, and microbes interact with mineral and organic matter to process soil carbon. Studies have been hampered by the difficulty of observing processes beneath the earth's surface, but advances in science and technology are improving our ability to understand belowground ecosystems.